Analysis of precursors to multiply controlled problem behavior: A replication. Issue 3 (29th May 2017) - Borlase, Megan A.; Vladescu, Jason C.; Kisamore, April N.; Reeve, Sharon A.; Fetzer, Jamie L.
Abstract : We replicated Fritz, Iwata, Hammond, and Bloom (2013) by evaluating the efficacy of an experimental methodology to identify precursors to aggression displayed by an adolescent with autism spectrum disorder. Using their trial‐based precursor analysis, we identified seven precursors to aggression. Next, we compared the outcomes of separate precursor and aggression functional analyses and showed that both precursors and aggression were multiply controlled by the same variables.